Strategi Pembinaan Dakwah Santri Di Pondok Pesantren Babul Hasanah Desa Maggis - Sahban Tua Simangunsong; Fatma Yulia (Jayapangus Press, 2023)
This research aims to find out the coaching strategy in improving the preaching of students at the Babul Hasanah Islamic Boarding School Batang Lubu Sutam district. This research uses a descriptive method with a qualitative approach. This research is a type of field research (field research) and literature (library research). Primary data sources were taken using data collection techniques in the form of interviews and observations in addition to secondary data as supporting data obtained indirectly. The data that has been collected by the researcher is then analyzed using techniques in the form of data reduction, data display and conclusions. The results of this study indicate that at the Babul Hasanah Islamic Boarding School, there are a series of activities that refer to improving the quality of students, both in terms of religion and their abilities. Da’wah coaching strategies carried out by pesantren through formal and non-formal activitiesby conducting a coaching that links a series of strategies, in order to achieve the desired goals. The coaching is stimulus in nature, namely the teacher designs special actions, implements them through a communication approach with the aim of influencing students. The coaching process that is carried out also includes the comfort of the students at the Babul Hasanah Islamic Boarding School, with these actions it is hoped that it can improve the students' preaching abilities at the Babul Hasanah Islamic Boarding school.